The Relationship Between Work Life Quality And Employee Performance - Ong, Chuan Huat; Ibrahim, Hazril Izwar (Yayasan Pendidikan Belajar Berdikari, 2023)
A company's human resources are a crucial asset since they may determine whether the business will still be around in the future. Different management guidelines are used by each business to ensure that its human resources function well. High performance productivity will be produced in the organization through effective performance management. Employee performance is influenced by a variety of variables, including experience and educational background. In order to gauge performance, researchers formulate the impact of human resource management as a problem. The purpose of this study is to determine how HRM impacts employee performance. Descriptive quantitative research design was utilized to describe the data from Alunicorn Hijab Bandung. Quality, quantity, timeliness, effectiveness, and independence are the characteristics that affect performance as determined by the scale of the indicators, according to the analysis's findings.